2000
DOI: 10.1097/00005537-200012000-00015
|View full text |Cite
|
Sign up to set email alerts
|

The Free Vascularized Flap and the Flap Plate Options: Comparative Results of Reconstruction of Lateral Mandibular Defects

Abstract: Objectives/Hypothesis: Reconstruction of the mandible and oral cavity after segmental resection is a challenging surgical problem. Although osteocutaneous free flaps are generally accepted to be optimal for reconstruction of anterior defects, the need for bony reconstruction for a pure lateral mandibular defect remains controversial. Study Design: A retrospective study. Methods: A retrospective comparative study of short-and long-term outcomes of three different reconstruction techniques for lateral defects wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…The use of a titanium plate with a soft tissue flap has been widely discussed. 16,17 The high rate of exposure, especially with through-andthrough defects and after radiation therapy, limits its application to small lateral and posterior mandibular defects, and only when a free bone-containing flap cannot be used. 18 In these cases, in order to limit exposure, fractures, and other plate-related complications, it is crucial to surround the plate with a large amount of revascularized tissue, thereby obliterating any dead space and ensuring adequate separation between the oral cavity, plate, and skin.…”
Section: Bone Defect Reconstructionmentioning
confidence: 99%
“…The use of a titanium plate with a soft tissue flap has been widely discussed. 16,17 The high rate of exposure, especially with through-andthrough defects and after radiation therapy, limits its application to small lateral and posterior mandibular defects, and only when a free bone-containing flap cannot be used. 18 In these cases, in order to limit exposure, fractures, and other plate-related complications, it is crucial to surround the plate with a large amount of revascularized tissue, thereby obliterating any dead space and ensuring adequate separation between the oral cavity, plate, and skin.…”
Section: Bone Defect Reconstructionmentioning
confidence: 99%
“…16 However, L and H defects reconstructed with soft tissue alone cause the mandible to drift toward the resected side, leading to restriction to a soft diet and change in appearance. 22 Ideal reconstruction follows the premise of replacing like with like; vascularized bone grafts provide the best functional and aesthetic results. However, in settings where the medical condition of the patient, the anatomy, or the intraoperative findings of peroneal thrombus prevent a free fibula f lap, an alternative method is needed.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5,7,11 Comparing 3 different reconstruction techniques for lateral mandibular defects (plate and pectoralis flap, plate and RFFF, and osteocutaneous flap), Shpitzer et al 2 reported that plates had to be removed in 7 of the 27 patients in the pectoralis flap group and 2 of the 16 patients in the FRFF group. None of the 14 osteocutaneous free flaps failed.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed reconstructive failure secondary to plate exposure or plate fracture has been reported to be between 5% and 46%. 2,[4][5][6][7] The use of an osteocutaneous free flap, in particular the osteocutaneous radial forearm free flap, likely reduces the risk of plate complication and offers the advantage of a large skin paddle that can be used to reconstruct nearly any accompanying mucosal defect. 8 The fibular osteocutaneous free flap offers the advantage that the cross-sectional area of the fibula approximates the cross-sectional area of the midbody of the mandible and is ideally suited for placement of osseointegrated implants for dental rehabilitation.…”
mentioning
confidence: 99%